A Study on Essence of Employee Engagement: An Organisational Perspective - Dr. Rajesh Kumar Pandey; Hetvi Kataria (International Journal of Engineering and Management Research, 2023)
Engagements in any form have been the crux of the cultural balance. The Organisations to a large extent aim to achieve this balance and engage the Employees in order to achieve Organisational goals. Employee engagement in an organization is massively related to the ability of an organization to manage its employees and generate high-performance levels. The key ingredients of an engaged employee seem to be a display of emotional involvement in what the employee does, and pride in the work place. Employee Engagement is seen as a powerful source of competitive advantage for companies in turbulent times. A deserving & good employee engagement is only going to happen if employees feel positive and strong about their relationship with their Superiors and the Organisation at large. The Researchers have adopted Exploratory & Descriptive Research design. The Research is conducted with the help of both Primary and Secondary data. The primary data is in the form of Interviews with Five Companies. The HR Heads were approached for the Interview. This Paper attempts to discuss on the Employee Engagement domain of Organisations. The Researchers aim to understand the essence & significance of Employee Engagement. The study further aims to study the factors influencing Employee Engagement at Organisations. The Researchers have gathered the Organisational perspective towards Employee Engagement and identified the relative challenges. The study encompasses the learning on Employee Engagement and understanding its essence. The Researchers have taken Employee Engagement aspect for Organisations at large rather any specific sector or region or set of Employee like Gender based etc., hence the inferences gathered are indicative in nature rather exhaustive. Employee Engagement is an essential virtue for Organisations and the same gets reflected through the Employee satisfaction, organizational success, and financial performance etc.